An Investigation into Cosmetic Market Strategy of China: A Case Study of Sephora - Gao Yifei (SHS Web of Conferences)
This paper investigates the Sephora’s consumer behaviors in Chinese market. With the larger segmentation of the market and changing consumer views of cosmetic products, there are factors of change in Consumer behavior. Sephora is a classic and successful representative in cosmetic industry for a long time, most of their marketing strategies are original and leading trend among most continents. However there has been a downturn in performance over the years. In order to determine the reasons for changes of the situation in recent years, this paper used case study method to analysing different perspectives of Sephora current marketing strategy. The review theoretical framework is based on 4Ps founded by Neil Borden, which applied with detailed explanations in four perspectives to reveal why Chinese market of Sephora are not performing well in last few years compare with the other marketing areas. In addition, three recommendations to correspondence issues divided in different aspects as increase local brands, improving brand awareness, integration into the local marketing market, adjusting price marketing model and business strategy.